Description of Post Anesthetic Shivering (PAS) in Post Spinal Anesthesia Caesarean Section - Rafifa, Tuffahati Naura; Rinal Effendi; Aladin (Andalas Obstetrics And Gynecology Journal, 2024)
Background: Post anaesthetic shivering (PAS) is a fasciculation of the face, jaw, or head or the occurrence of muscle hyperactivity so that the body can produce heat after anesthesia. Multiple factors can influence the incidence of PAS including age, sex, ASA physical status, body mass index, type of anesthesia, duration of surgery, room temperature, preoperative body temperature (<36,5â°C), and type of surgery.  Objective : The purpose of this study was to describe the incidence of PAS in post-spinal anesthesia caesarean section patients at RSIA Siti Hawa Padang Method: This research is a descriptive observational study using accidental sampling technique and obtained a total sample of 52 patients Result: The result showed that 25 of 52 patients (48,1%) experienced PAS. Most PAS events were experienced by moderate grade (25%), the age group >35 years (60%), underweight body mass index (62,5%), ASA II status (52,2%), preoperative temperature in the hypothermia group (51,4%), postoperative temperature in the normothermia group (66,7%), and operation duration >30 minutes (57,1%) Conclusion: Most of the patients did not experience PAS and most of PAS experience was moderate grade.